2016
DOI: 10.15448/1984-7289.2016.2.23066
|View full text |Cite
|
Sign up to set email alerts
|

Vitimização letal e desigualdade no Brasil: evidências em nível municipal

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4. Abstract: This paper deals with the relation between lethal violence and inequality under two approaches. The first one is the inequality in the risk of becoming a victim of homicide among various kinds of people. In this sense, the profile of victims of lethal violence in Brazil is very clear: young black males. The second approach concerns the relation between inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 3 publications
(3 reference statements)
1
14
0
6
Order By: Relevance
“…10 This movement towards the outskirts probably occurred because of the unequal distribution of State interventions, following the global trend of violent events, such as intentional homicides tending to occur in economically disadvantaged places. [2][3][4]16,18,19,[23][24][25][26][27][28][29] Although the data used in this study were retrieved from official information systems, they are subject to information bias, given the process that takes place between the occurrence of the event and the data being input on the systems. The first limitation of this study is underreporting which is reflected in the reduction in the number of deaths reported because of burials taking place without the required notification being made.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 This movement towards the outskirts probably occurred because of the unequal distribution of State interventions, following the global trend of violent events, such as intentional homicides tending to occur in economically disadvantaged places. [2][3][4]16,18,19,[23][24][25][26][27][28][29] Although the data used in this study were retrieved from official information systems, they are subject to information bias, given the process that takes place between the occurrence of the event and the data being input on the systems. The first limitation of this study is underreporting which is reflected in the reduction in the number of deaths reported because of burials taking place without the required notification being made.…”
Section: Discussionmentioning
confidence: 99%
“…This data comes from various sources, such as Public Security and Health services. 2,16,17 In addition, although the SIM database provides information about the location of the occurrence of death, it provides no data on the place where the violent event that preceded death occurred. The SESDS/PB database overcomes this shortcoming by providing georeferenced information on this place.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations